Carbon-based superconductors : toward high-Tc superconductivity - Haruyama, Junji (CRC Press : Pan Stanford Publishing, 2015)
Superconductors (SCs) are attractive materials in all respects for any community. They provide a deep insight into the physical properties of the condensed matters and also have useful applications as ultra-low-power-dissipation systems that can help resolve the present energy problems. In particular, the recent advancement of carbon-based new superconductors (CNSCs) is significant. Before 2004, the superconducting transition temperature (Tc) of carbon-based SCs was below 1 K, except in fullerene clusters. However, in 2004, a Russian group discovered that diamond highly doped with boron could.